Impact of vitamin D therapy on decreasing of proteinuria in type 2 diabetic patients - Ali Momeni; Mahmood Mirhosseini; Mohsen Kabiri; Soleiman Kheiri (Society of Diabetic Nephropathy Prevention, 2017)
Background: Vitamin D (Vit D) deficiency is a common disorder in diabetic patients and may be a risk factor for ischemic heart disease and exacerbation of diabetic nephropathy(DN). Objectives: The aim of this study was to evaluate the effect of Vit D3 therapy on protein uriain type 2 diabetic patients with deficient or insufficient serum Vit D. Patients and Methods: In a double blind clinical trial, 60 type 2 diabetic patients with proteinuria greater than 150 mg/day who had Vit D deficiency or insufficiency were randomly enrolled in two equal groups. Pearl of Vit D as 50 000 IU/week and placebo (1 tablet per week) were prescribed in patients of case and control groups respectively for 8 weeks. At the beginning and 2 months later, 24 hours urine protein was checked in all patients. Results: There is no difference between serums Vit D level in case and control group at the beginning of the study, however at the end of the study serum Vit D level was significantly higher in the case group. There is no difference in proteinuria between case and control group at the beginning and the end of the study, while a significant difference between the changes of proteinuria before and after the study was seen in two groups (P = 0.028). Conclusions: Vit D deficiency may exacerbate protein uric and DN, hence correction of Vit D deficiency may decrease proteinuria in diabetic patients with nephropathy.